2016
DOI: 10.3109/02656736.2016.1155761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperthermia in neutralising mechanisms of drug resistance in non-muscle-invasive bladder cancer

Abstract: Non-muscle-invasive bladder cancer is a challenging disease, even given its superficial nature. It is prone to multiple recurrences and progression to muscle-invasive cancer. These features of this disease contribute significantly to reduced quality of life as well as creating significant morbidity and even mortality. Randomised trials demonstrate that when hyperthermia is added to conventional mitomycin-C treatment that local control rates and progression-free survival are substantially improved. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 81 publications
(112 reference statements)
0
23
1
Order By: Relevance
“…In the present study, both BHPC and intravesical chemotherapy achieved high local drug concentrations in the perfusion liquid, thus, at the intravesical cavity of the bladder, but serum concentrations of MMC were maintained below those associated with systematic administration of the drug. Although, the serum MMC concentrations in the BHPC group were significantly higher than those in the intravesical perfusion chemotherapy group in the present study, it did not reach sufficiently high levels to cause serious adverse effects (21,34,35). The advantages of BHPC over single intravesical chemotherapy can be attributed to the synergy of local hyperthermia treatment and chemotherapy.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In the present study, both BHPC and intravesical chemotherapy achieved high local drug concentrations in the perfusion liquid, thus, at the intravesical cavity of the bladder, but serum concentrations of MMC were maintained below those associated with systematic administration of the drug. Although, the serum MMC concentrations in the BHPC group were significantly higher than those in the intravesical perfusion chemotherapy group in the present study, it did not reach sufficiently high levels to cause serious adverse effects (21,34,35). The advantages of BHPC over single intravesical chemotherapy can be attributed to the synergy of local hyperthermia treatment and chemotherapy.…”
Section: Discussioncontrasting
confidence: 72%
“…This result suggested that bladder mucosal wound by TUR of bladder carcinoma did not increase the absorption of chemotherapeutic drugs. In addition, the plasma half-life of MMC is 30-50 min (34,35), and we found that the serum MMC concentration remained stable during BHPC, but rapidly declined after BHPC. We hypothesized that absorption of chemotherapeutic drugs compensated for metabolism of chemotherapeutic drugs during BHPC The aim of BHPC treatment post-TUR is to cause maximal killing of residual tumors, with minimal damage to normal tissues.…”
Section: Discussionmentioning
confidence: 71%
“…88 Activation of cell death pathways, direct damage to proteins responsible for drug resistance, and enhanced drug delivery are the most important mechanisms by which PDT mediates the reversing of MDR. 89…”
Section: Physical Approaches To Overcome Mdrmentioning
confidence: 99%
“…The dynamic model presented in this article significantly improves temperature predictions of bladder (wall) temperatures, which provides opportunities for further clinically related research and improvement of quality assurance. As temperature is correlated to penetration depth of the chemotherapeutic instillation [50], future research will include a study of the relation between hyperthermic dose and clinical effect, taking into particular account the relation between temperatures measured in the bladder, the computed temperature in the bladder wall, and the therapeutic benefit.…”
Section: Muscle-likementioning
confidence: 99%